The complete mitochondrial genome of Psyttalia incisi (Silvestri, 1916) (Hymenoptera: Braconidae). Issue 6 (3rd June 2022) - Yang, Deqing; Hao, Xuxing; Jiang, Lili; Chou, Tsunglin; Lin, Xiang; Yue, Guoqing; Xiao, Kang; Lin, Jia; Ji, Qinge; Cai, Pumo
Abstract: Psyttalia incisi (Silvestri, 1916), an important solitary opiinae endoparasitoid, plays a crucial role in biological control programs against tephritid pests. In this study, the entire mitochondrial (mt) genome of P. incisi was sequenced and characterized. The whole mitogenome of P. incisi is 15, 188 bp long with a G + C content of 14.80%, and encodes all 37 genes that are typically found in animal mt genomes, which contains 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and two ribosomal RNA genes (rRNAs). A maximum-likelihood (ML) tree demonstrates that P. incisi is closely related to Psyttalia lounsburyi, Psyttalia humilis, and Psyttalia concolor .